Cover Feature: The Synthesis of Chiral γ‐Lactones by Merging Decatungstate Photocatalysis with Biocatalysis (ChemCatChem 19/2022). Issue 19 (13th September 2022) - Özgen, Fatma Feyza; Jorea, Alexandra; Capaldo, Luca; Kourist, Robert; Ravelli, Davide; Schmidt, Sandy
Abstract : The Cover Feature illustrates how dual catalysis between a photocatalyst and an enzyme accomplishes the synthesis of chiral γ‐lactones from simple starting materials. In their Research Article, D. Ravelli, S. Schmidt and co‐workers explored a decatungstate photocatalyst that, upon near‐UV light irradiation, promotes the radical hydroacylation of α, β‐unsaturated esters or acids with aldehydes. Subsequently, an alcohol dehydrogenase reduces the intermediate keto esters/acids to the corresponding chiral alcohols, which undergo lactonization to the desired chiral γ‐lactones. This study highlights the powerfulness of merging photo‐ with biocatalysis for building molecular complexity to access high‐value added chiral compounds from simple, cheap, and largely available starting materials. More information can be found in the Research Article by D. Ravelli, S. Schmidt and co‐workers .